Implementation of Tel Aviv University MOOCs in Academic Curriculum: A Pilot Study - Soffer, Tal; Cohen, Anat (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
The study presented in this paper examines the feasibility of using MOOCs as a learning environment in academic courses. This paper focuses on the students who participated in two MOOCs offered by Tel Aviv University (TAU) during the year 2013. The preliminary findings of this pilot study illustrate the scope of student activity, the learning intensity, and learner path. In addition, attitudes of TAU students who participated in these courses as part of their curriculum are presented. From TAU’s perspective, the presented MOOCs are considered to be a successful experience for all those involved: the students, who were very satisfied with their learning and high achievements; the lecturer team, who were very enthusiastic and satisfied with the learning process as well as the new experience; and the University policy makers, who took the challenge and integrated this new model of learning into the academic environment.